Innate immunity as a target for novel therapeutics in triple negative breast cancer. (3rd August 2022) - Borgovan, Theo; Yanamandra, Niranjan; Schmidt, Hank
ABSTRACT: Introduction: Currently, triple-negative breast cancer (TNBC) has limited therapeutic options beyond chemotherapy and has worse outcomes than other breast cancer subtypes. Initial experience with immune checkpoint blockade for the treatment of TNBC has indicated that modifying the tumor immune response represents a promising direction of investigation. Subsequent studies have led to a deeper understanding of the heterogeneity of this disease and have informed further exploration of numerous potential therapeutic approaches to intervene in the tumor microenvironment (TME). Areas covered: Initial work in this arena has focused on enhanced definition of checkpoints in activation of an adaptive immune response. In this review, we discuss recent efforts that have looked into components of innate immunity to reverse immunosuppressive phenotypes and augment antitumor immune response. Expert opinion: Current treatment options for TNBC have been improved with the approval of immune checkpoint inhibitors (ICI) in both advanced and early-stage disease; however, the challenge remains to expand the number of patients that will benefit from immunotherapy. Optimizing the innate immune response represents an opportunity to improve this therapeutic index, and the development of an array of novel agents is underway. Success will depend on precision characterization of the patient TME and selection of ideal combination therapy.